2016
DOI: 10.1089/tmj.2015.0124
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability Study of “Ascenso”: An Online Program for Monitoring and Supporting Patients with Depression in Chile

Abstract: ASCENSO appears to be a promising complement to regular care for depression. Following improvements of the program based on participants' feedback, future research should evaluate its efficacy and cost-effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 17 publications
0
20
0
4
Order By: Relevance
“…37 Two pilot studies from Chile showed the acceptability of online depression treatment, including an online video game for supporting depression treatment among adolescents 38 and an online programme for symptom monitoring in patients receiving treatment for major depression. 39 An exploratory study 40 also showed that SMS text-messaging was feasible and acceptable for promotion of positive mental health in young women living in urban slums in Bangalore, India.…”
Section: Resultsmentioning
confidence: 99%
“…37 Two pilot studies from Chile showed the acceptability of online depression treatment, including an online video game for supporting depression treatment among adolescents 38 and an online programme for symptom monitoring in patients receiving treatment for major depression. 39 An exploratory study 40 also showed that SMS text-messaging was feasible and acceptable for promotion of positive mental health in young women living in urban slums in Bangalore, India.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in the evaluation of this program, Parada et al (38) suggested using a persuasive systems design approach. Likewise, in the study of Espinosa et al (32) participants who had completed the intervention suggested diversifying the monitoring assessments and having the possibility to interact with a therapist from the treatment center where they underwent face-to-face treatment. Both Martínez et al (under review) and Espinosa et al (32) suggested enabling peer communication.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, in the study of Espinosa et al (32) participants who had completed the intervention suggested diversifying the monitoring assessments and having the possibility to interact with a therapist from the treatment center where they underwent face-to-face treatment. Both Martínez et al (under review) and Espinosa et al (32) suggested enabling peer communication. ASCENSO and CTA studies showed that email does not seem to be a good way to contact and monitor participants (27,29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some systems offer interactive self-help with psychotherapy/psychoeducation [9], some include clinical backup, some are designed for use on smartphones, and others are designed for computers or tablets [10]. A small number of systems use a bidirectional feedback loop between patients and clinicians [11,12], in which data entered by patients can be seen in real-time by the clinician, and responses can occur immediately if needed. These systems make it easier for patients and clinicians to notice changes in conditions over time, be it behavioral changes such as activity or medication, or psychopathological symptoms (eg, mood and sleep).…”
Section: Introductionmentioning
confidence: 99%